Investigating the linguistic effectiveness of early reading schemes in isiXhosa: a phonological and orthographical analysis of three isiXhosa Grade 1 graded reader series - Katz, Jennifer L (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2019)
Literacy in South Africa is in crisis. Inadequate learning and teaching materials, extensive curriculum changes, under-resourced schools and under-qualified teachers are all contributing factors to an alarming situation. Grade 1 African language reading schemes in South Africa are failing to provide young children with the necessary and appropriate practice required to facilitate home language literacy acquisition (NEEDU 2013). A detailed analysis of three isiXhosa Grade 1 graded reader series will show the short-comings of texts translated from English with no cognisance of isiXhosa phonic structures and little appreciation for the agglutinative nature of Nguni languages. Formulating a new, effective approach to the development of African language readers to facilitate reading literacy is urgent and of national importance. The innovative phonics-based methodology, as well as an appropriate instructional level used to develop the Vula Bula Grade 1 isiXhosa readers appears to be a viable blueprint for the development of early readers that can effectively help to ameliorate current deficient literacy levels in African languages. This research thus combines applied linguistics with literacy materials development.
Keywords: Education, Elementary -- South Africa; Literacy -- South Africa; Xhosa language -- Readers; Native language and education -- South Africa